A Novel Postbiotic Reduces Canine Halitosis - Aylesse Sordillo; Liza Casella; Raphaël Turcotte; Ravi U. Sheth (Animals)
A majority of dogs suffer from some form of periodontal disease. This frequently manifests as halitosis or oral malodor, caused by microbes underlying poor oral health. Pathogenic oral microbes process dietary or host proteins into volatile sulfur compounds (VSCs), which are perceived as malodorous and can further contribute to inflammation and periodontal disease progression. This double-blind, placebo-controlled, randomized clinical trial evaluated the ability of Superculture® Pet Oral, a novel canine oral health postbiotic (COHP), to reduce canine oral malodor. In total, 24 dogs were stratified into two groups based on starting VSC levels. The groups received either COHP or a placebo as a powder topper for 14 days. VSC levels were measured via a Halimeter on Days 0, 7, and 14. Perceived malodor was also scored on the same days. COHP significantly decreased VSCs from baseline by Day 7 by 22% (p = 0.002). In the placebo group, VSCs increased over the course of the study. Throughout the study, COHP lowered VSC levels by 27% compared to the placebo (p = 0.004), and fully prevented an increase in VSCs compared to the baseline. Additionally, VSCs were correlated with the human perception of malodor, and twice as many dogs in the COHP group had perceptibly improved breath on Day 7 compared to the placebo, measured through a 10-point scaled survey. These findings validate the ability of this novel postbiotic to effectively reduce canine oral malodor and provide preliminary evidence that it may more broadly help to maintain canine oral health.